2015
DOI: 10.1152/jn.00569.2014
|View full text |Cite
|
Sign up to set email alerts
|

Comparative diffusion tractography of corticostriatal motor pathways reveals differences between humans and macaques

Abstract: The primate corticobasal ganglia circuits are understood to be segregated into parallel anatomically and functionally distinct loops. Anatomical and physiological studies in macaque monkeys are summarized as showing that an oculomotor loop begins with projections from the frontal eye fields (FEF) to the caudate nucleus, and a motor loop begins with projections from the primary motor cortex (M1) to the putamen. However, recent functional and structural neuroimaging studies of the human corticostriatal system re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 41 publications
4
23
0
Order By: Relevance
“…First, although FA is the most commonly used measure of white matter integrity, it is influenced by a range of biological factors, including myelination, axonal r White Matter Integrity and Cognitive Control Speed r r 2819 r damage, axonal diameter, and fiber coherence [Assaf and Pasternak, 2008] Thus, the precise physiological underpinnings of the current findings cannot be specified; however, since this is a group of healthy, young participants, we find it unlikely that individual differences in axonal damage are driving behavioral correlations. The tracts connecting cortical regions with caudate and putamen were largely overlapping, consistent with a recent study comparing these tracts between macaques and humans [Neggers et al, 2015]. That is, we cannot say whether behavior is related to connections from region A to region B, from region B to region A, or both.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…First, although FA is the most commonly used measure of white matter integrity, it is influenced by a range of biological factors, including myelination, axonal r White Matter Integrity and Cognitive Control Speed r r 2819 r damage, axonal diameter, and fiber coherence [Assaf and Pasternak, 2008] Thus, the precise physiological underpinnings of the current findings cannot be specified; however, since this is a group of healthy, young participants, we find it unlikely that individual differences in axonal damage are driving behavioral correlations. The tracts connecting cortical regions with caudate and putamen were largely overlapping, consistent with a recent study comparing these tracts between macaques and humans [Neggers et al, 2015]. That is, we cannot say whether behavior is related to connections from region A to region B, from region B to region A, or both.…”
Section: Discussionsupporting
confidence: 84%
“…Interestingly, this overlap in connections r White Matter Integrity and Cognitive Control Speed r r 2815 r between cortex and PUT and CN dovetails with a recent study from Neggers et al [2015] who found that DTI tracts from the FEF terminated both in PUT and CN (with a dominance for PUT in humans), a finding contradicting the classically held view of the CN as oculomotor striatum [Alexander et al, 1986]. For example, the size of the seed ROI plays an important role in determining connectivity values.…”
Section: Probabilistic Tractographymentioning
confidence: 61%
See 1 more Smart Citation
“…Rilling et al (2008) described an enhanced frontotemporal component of the arcuate fasciculus in humans, possibly related to language functions. Neggers et al (2015) described more extensive overlap between eye field and M1 projections to the striatum in humans than in monkey.…”
Section: Dt Topographymentioning
confidence: 93%
“…4; Table II). However this might be related to the fact that these connections are mainly indirect through corticostriatal-motor and cortico-thalamic pathways [Guye et al, 2003;Neggers et al, 2015]. Also, the insula is anatomically variable [Rosen et al, 2015] and its connections are regionally-selective (e.g.…”
Section: Nces Are Correlated To An Mpfc-insula-motor Cortex Networkmentioning
confidence: 99%